Treatment of dyslipidemia in patients with type 2 diabetes - Vijayaraghavan Krishnaswami (Lipids in Health and Disease, 2010)
Abstract Type 2 diabetes is associated with significant cardiovascular morbidity and mortality. Although low-density lipoprotein cholesterol levels may be normal in patients with type 2 diabetes, insulin resistance drives a number of changes in lipid metabolism and lipoprotein composition that render low-density lipoprotein cholesterol and other lipoproteins more pathogenic than species found in patients without type 2 diabetes. Dyslipidemia, which affects almost 50% of patients with type 2 diabetes, is a cardiovascular risk factor characterized by elevated triglyceride levels, low high-density lipoprotein cholesterol levels, and a preponderance of small, dense, low-density lipoprotein particles. Early, aggressive pharmacological management is advocated to reduce low-density lipoprotein cholesterol levels, regardless of baseline levels. A number of lipid-lowering agents, including statins, fibrates, niacin, and bile acid sequestrants, are available to target normalization of the entire lipid profile. Despite use of combination and high-dose lipid-lowering agents, many patients with type 2 diabetes do not achieve lipid targets. This review outlines the characteristics and prevalence of dyslipidemia in patients with type 2 diabetes and discusses strategies that may reduce the risk of cardiovascular disease in this population.